Crypto Laundering: An Analysis from a Game Theory Perspective - Matos Rodrigues, Iagor; Hendryk Pereira de Almeida, Ryan; Silva de Paiva, Matheus (Revista Gestão do Conhecimento e Tecnologia da Informação, 2024)
Cryptocurrencies have revolutionized the financial sector by enabling decentralized electronic transactions that bypass traditional intermediaries. However, their anonymous nature has led to growing concerns about their use in money laundering, sparking an increase in illicit activities. This article investigates this issue, focusing on the role of cryptocurrency exchanges and the regulatory challenges they pose. By applying game theory, the study analyzes the incentives and strategies of various agents involved and explores potential regulatory and preventative measures to curb illicit behavior within the global financial system. We find that effective regulation is essential to prevent misuse of cryptocurrencies, but it must be carefully balanced. Overly stringent measures could undermine the economic potential of cryptocurrencies, preventing them from real-izing their full market potential. Governments should focus on adaptable frameworks that promote innovation while addressing risks, ensuring that cryptocurrencies can thrive without becoming tools for illicit activities.